Virtual realities: The use of violent video games in U.S. military recruitment and treatment of mental disability caused by war - Derby, John (Disability Studies Quarterly, 2016)
This article critically analyzes the U.S. military's contradictory use of violent video gaming technologies for recruiting young gamers to the military, training soldiers for combat, and clinically treating soldiers for posttraumatic stress disorder (PTSD) caused by military service. Using a Disability Studies lens, I discuss the commercial video game Full Spectrum Leader/Warrior, the U.S. Army's free video game America's Army, and the virtual reality exposure therapy application Virtual Iraq. I also discuss missions and omissions from the literature on these gaming technologies, which bolsters the underlying ableism of military culture that inhibits soldiers from recovering from PTSD.